Social sector in a decentralised economy : India in the era of globalisation - Chakraborty, Pinaki (Cambridge University Press, 2016)
""Provides critical insights into the effectiveness of public expenditure through benefit incidence analysis of education and healthcare services in India"--Provided by publisher"--